Longitudinal Monitoring of EGFR and PIK3CA Mutations by Saliva-Based EFIRM in Advanced NSCLC Patients With Local Ablative Therapy and Osimertinib Treatment: Two Case Reports - Li, Ning; Guha, Udayan; Kim, Chul; Ye, Leah; Cheng, Jordan; Li, Feng; Chia, David; Wei, Fang; Wong, David T. W. (Frontiers in Oncology, 2020)
Background: The longitudinal monitoring of actionable oncogenes in circulating tumor DNA (ctDNA) of non-small cell lung cancer (NSCLC) is crucial for clinicians to evaluate current therapeutic response and adjust therapeutic strategies. Saliva-based electric field–induced release and measurement (EFIRM) is liquid biopsy platform to that can directly detect mutation genes with a small volume of samples. Herein, we compared the effectiveness of longitudinal monitoring for the combination of epidermal growth factor receptor (EGFR) and phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) mutations between saliva-based EFIRM and plasma-based platforms (ddPCR and NGS) in two advanced NSCLC patients undergoing the treatment with osimertinib before and after local ablative therapy (LAT). Patients and Methods: Two patients with unresectable advanced NSCLC were enrolled into the National Institutes of Health Clinical Center (NIHCC) Study (ClinicalTrials.gov: 16-C-0092; local ablative therapy for the treatment of oligoprogressive, EGFR-mutated, non-small cell lung cancer after treatment with osimertinib). Serial collections of saliva, plasma, and metastatic tumor volume measurement by computed tomography (CT) were performed. Longitudinal paired saliva and plasma samples were analyzed for p.L858R EGFR, exon19 del EGFR, and p.E545K PIK3CA ctDNA using EFIRM (saliva) and ddPCR and NGS (plasma). Results: In Case. 1, the saliva ctDNA curve of exon19 del EGFR by EFIRM demonstrated a strong similarity to those of tumor volume (R = 0.78, P = 0.00) and exon19 del EGFR in ddPCR (R = 0.53, P = 0.01). Moreover, the curve of p.E545K PIK3CA in EFIRM showed similarity to those of tumor volume (R = 0.70, P = 0.00) and p.E545K PIK3CA in NGS (R = 0.72, P = 0.00). In Case. 2, the curve of p.E545K PIK3CA in EFIRM revealed a reverse relationship to that of tumor volume (R = -0.65, P = 0.01). Conclusion: In these two case reports, saliva-based EFIRM platform demonstrates a high level of concordance to plasma-based platforms (ddPCR and NGS) for longitudinally monitoring the combination of EGFR and PIK3CA ctDNA and can be a useful platform to monitor tumor progression and response to targeted therapy in NSCLC patients.